Kajian komposit plastik daur ulang dengan serbuk kayu untuk bahan bangunan - Yuniari, Arum (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2007)
The require problem were wood as building material either for material, decoration, or furniture increases along with the raise of population. Composite is a material which is formed by two or more distinctive components united. The manufacturing of composite made of recycle plastic and wood flour is aimed to lower environmental encumbering and produce a kind of product for building material. Composite of recycle plastic and wood flour is that made of recycle plastic as the matrix and wood flour as the filler, and expected being able to adopt both properties. The process of composite manufacturing was carried-out through the phase of preparation for filler, plastic recycle, mixing, pelletizing, and product manufacturing. It can be concluded from the review that the quantity, type of wood selected, size of wood flour prepared, water content, and quantity of compatibilizer affect very much upon the quality of composite produced. Composite produced of plastic recycle and wood flour by applying certain technology can be used for material building.Â Keywords: composite, recycle plastic, wood-flourÂ RINGKASANKebutuhan masyarakat akan kayu untuk keperluan bahan bangunan, dekorasi maupun mebeler terus meningkat seiring dengan meningkatnya jumlah penduduk. Komposit merupakan bahan yang dibuat dari dua atau lebih penggabungan komponen yang berlainan. Pemanfaatan komposit plastik daru ulang dan serbuk kayu dimaksudkan untuk menguragi pencemaran lingkungan dan menghasilkan produk yang bermanfaat untuk pemenuhan kebutuhan bahan bangunan. Komposit plastik daur ulang dan serbuk kayu adalah komposit yang terbuat dari plastik daur ulang sebagai matriks dan serbuk kayu sebagai bahan pengisi (filler). Komposit diharapkan mempunyai sifat lebih baik dari masing-masing sifat yang dimiliki oleh plastik daur ulang maupunm serbuk kayu. Pembuatan komposit dilaksanakan melalui tahap penyiapan bahan pengisi, daur ulang plastik, pencampuran, pelletizing dan pembuatan produk. Dari hasil kajian dapat disimpulkan bahwa jumlah, jenis kayu, ukuran serbuk kayu, kadar air dan jumlah compatibilizer sangat mempengaruhi kualitas komposit. Komposit plastik daur ulagn dan serbuk kayu dengan teknologi tertentu dapat dimanfaatkan untuk bahan bangunan.Â Kata Kunci : komposit, plastik daur ulang, serbuk kayu.